Cover Image. Issue 10 (27th September 2022) - Unknown
Abstract : To illustrate electrical stimulation of nerve roots emerging from the cervical spine, we decided to show a person from the side, with electrodes on the skin surface. I superimposed imaginary electric currents that are generated by these electrodes and visualized them as illuminating light